Mandibular ramus shape variation and ontogeny in Homo sapiens and Homo neanderthalensis. Issue 121 (August 2018) - Terhune, Claire E.; Ritzman, Terrence B.; Robinson, Chris A.
Abstract: As the interface between the mandible and cranium, the mandibular ramus is functionally significant and its morphology has been suggested to be informative for taxonomic and phylogenetic analyses. In primates, and particularly in great apes and humans, ramus morphology is highly variable, especially in the shape of the coronoid process and the relationship of the ramus to the alveolar margin. Here we compare ramus shape variation through ontogeny in Homo neanderthalensis to that of modern and fossil Homo sapiens using geometric morphometric analyses of two-dimensional semilandmarks and univariate measurements of ramus angulation and relative coronoid and condyle height. Results suggest that ramus, especially coronoid, morphology varies within and among subadult and adult modern human populations, with the Alaskan Inuit being particularly distinct. We also identify significant differences in overall anterosuperior ramus and coronoid shapes between H. sapiens and H. neanderthalensis, both in adults and throughout ontogeny. These shape differences are subtle, however, and we therefore suggest caution when using ramus morphology to diagnose group membership for individual specimens of these taxa. Furthermore, we argue that these morphologies are unlikely to be representative of differences in masticatory biomechanics and/or paramasticatory behaviors between Neanderthals and modern humans, as has been suggested by previous authors. Assessments of ontogenetic patterns of shape change reveal that the typical Neanderthal ramus morphology is established early in ontogeny, and there is little evidence for divergent postnatal ontogenetic allometric trajectories between Neanderthals and modern humans as a whole. This analysis informs our understanding of intraspecific patterns of mandibular shape variation and ontogeny in H. sapiens and can shed further light on overall developmental and life history differences between H. sapiens and H. neanderthalensis .